2018
DOI: 10.1080/1354750x.2018.1531929
|View full text |Cite
|
Sign up to set email alerts
|

Hair follicle miRNAs: a novel biomarker for primary blast Induced-Mild traumatic brain injury

Abstract: Context Due to the wide use of improvised explosive devices during modern warfare, primary blastderived mild traumatic brain injury (mTBI) has become a major medical condition in the military. With minimal visually identifiable symptoms, an effective molecular biomarker system is desirable. Objective We assessed the potential of mammalian hair follicle miRNAs as an mTBI biomarker. Materials and methods Due to their well-established roles in mTBI molecular pathology, the expression level of miR-183, miR-26a, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A biomarker test that was FDA-approved in 2018, known as The Brain Trauma Indicator, measures acute levels of UCH-L1 and GFAP in concussed individuals and provides the hope of reducing the need for unnecessary CT scans by prediction of intracranial lesions ( 132 ). A less mainstream approach to identify biomarkers involves the study of mammalian hair follicles that demonstrated unique subnetworks of miRNA following mTBI ( 133 ). As considerable inconsistencies exist pertaining to blast TBI, one of the main research goals of preclinical blast TBI studies is to aid the development of assays for highly reliable blood biomarkers.…”
Section: Biomarker Development and Treatment Approaches For Blast-induced Tbimentioning
confidence: 99%
“…A biomarker test that was FDA-approved in 2018, known as The Brain Trauma Indicator, measures acute levels of UCH-L1 and GFAP in concussed individuals and provides the hope of reducing the need for unnecessary CT scans by prediction of intracranial lesions ( 132 ). A less mainstream approach to identify biomarkers involves the study of mammalian hair follicles that demonstrated unique subnetworks of miRNA following mTBI ( 133 ). As considerable inconsistencies exist pertaining to blast TBI, one of the main research goals of preclinical blast TBI studies is to aid the development of assays for highly reliable blood biomarkers.…”
Section: Biomarker Development and Treatment Approaches For Blast-induced Tbimentioning
confidence: 99%
“…Several miRNAs were upregulated or downregulated in injured versus control mice21 and changes in miR-21 occurred between TBI severities 22. One study assessed mammalian hair follicle miRNAs (rat whiskers) as an mTBI biomarker and found that 6 miRNAs within TBI molecular networks were disrupted after TBI23 (see Table 1, see Supplemental Digital Content Table 4, available at: http://links.lww.com/JHTR/A373).…”
Section: Resultsmentioning
confidence: 99%
“…The most downregulated miRNA at the 2-h timepoint (fold change−7.65), miR-181c-5p, maintained more than a 5-fold reduction after 18 h from concussion and almost 3-fold at the end of the season. Interestingly, one study reported that miR-181c-5p was part of miRNA signature for primary blast-induced mild TBI evaluated in hair follicles ( 46 ). We also found that miR-17-5p was significantly downregulated near or >3-fold at every timepoint, including the end of the season.…”
Section: Discussionmentioning
confidence: 99%